The Exploration Of Directive Illocutionary Act In “The Pursuit Of Happyness” Movie - Nugraha, I Putu Gede Aditya; Suastra, I Made; Maharani, Sang Ayu Isnu (Denpasar Institute, 2024)
According to Austin (1962:1) “a statement can only be to describe some state of affairs, or to state some fact, which it must do either truly or falsely. It have been regularly pointed out that not all sentences are used in making statements.” Leech (1983:13) “context deals with relevant aspect of physical or social setting of an utterance. Therefore, social setting in this case comes from the speaker and the listener.” Lyons (1977:34) states that “A clear difference can happen between the listener (the person who receives and interprets the utterance) and the speaker (the person to whom the utterance is delivered).” This research entitled The Exploration of Directive Illocutionary Acts In “The Pursuit of Happyness” Movie is aimed to analyze the context of situation of directive illocutionary act that indicate directive illocutionary act found in “The Pursuit of Happyness” movie script and identify the types of directive illocutionary act found in “The Pursuit of Happyness” movie script. Documentation and observation method were applied in conducting this study. Descriptive qualitative method was applied in analysing the data in this study. Informal method was used in presenting the final result of the analysis. The research findings showed that there were a total of eighteen scenes in the movie “The Pursuit of Happyness” which indicate the directive illocutionary acts. There were six types of directive illocutionary acts in the movie “The Pursuit of Happyness”: Request, Question, Prohibition, Requirement, Permission, and Advice